Some aspects of the pathology of trophoblast - Fernandes, Martiniano (2015)
The incidence of mola hidatiforme and choriocarcinoma in our Service has presented more likelihood to data as suggested by European and American statistics, than to evaluations provided by European and American statistics, than to evaluations provided by Asiatic authors (Novak - Hertig - Brindeau - Acosta Sisson and Cartroux). Hemorrhage has been the outstanding simptom among patients suffering of mola hidatiforme and treatment in our Service has been carried out as follows: curage, either single or sometimes followed by immediate curetage, the latter being post-poned to 4 or 5 years later in certain instances.